2005
DOI: 10.2527/2005.8371633x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary magnesium and short-duration transportation on stress response, postmortem muscle metabolism, and meat quality of finishing swine1

Abstract: Crossbred pigs, heterozygous for the halothane gene, were used to determine the effects of long-term dietary supplementation of magnesium mica (MM) and short-duration transportation stress on performance, stress response, postmortem metabolism, and pork quality. Pigs were blocked by weight, penned in groups (six pigs per pen), and pens (three pens per diet) were assigned randomly either to a control corn-soybean meal diet or the control diet supplemented with 2.5% MM (as-fed basis; supplemented at the expense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
9
32
2
1
Order By: Relevance
“…The magnesium and lactic acid concentration do not show any effects from the dietetic supplementation with MgO during the last week before the slaughter. This is similar to the observed by Apple et al (2005) that reported no alteration on serum magnesium concentration by a dietetic supplementation with magnesium mica in animals submitted to stress by transportation. However, D'Souza et al (1998) reported evidences that the supplementation with magnesium aspartate for swine reduce the acid lactic concentration in the muscular tissue 40 minutes before slaughter, that mean a reduced stress effect on the muscular glycogenolysis.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The magnesium and lactic acid concentration do not show any effects from the dietetic supplementation with MgO during the last week before the slaughter. This is similar to the observed by Apple et al (2005) that reported no alteration on serum magnesium concentration by a dietetic supplementation with magnesium mica in animals submitted to stress by transportation. However, D'Souza et al (1998) reported evidences that the supplementation with magnesium aspartate for swine reduce the acid lactic concentration in the muscular tissue 40 minutes before slaughter, that mean a reduced stress effect on the muscular glycogenolysis.…”
Section: Resultssupporting
confidence: 80%
“…Peeters, Driessen and Geers (2006) also treat swine with Mg (by water) and do not have significant results for initial and final pH values. In a contrary way, Apple et al (2005) found in swine transported during 3 hours and supplemented with magnesium mica a higher initial pH value that those ones not submitted to transportation independently from consumed diet; however the final pH measures were not affected by the treatments. The water retention capacity is a very important characteristic because affect the appearance of meat before cooking, the behavior during the cooking process, the juiciness during the chew process and the technologic yield for preparation of meat products (LAWRIE, 2005).…”
Section: Mgo Inclusion On Feed (%)mentioning
confidence: 57%
See 1 more Smart Citation
“…Concentrations of most plasma metabolites were different between pretransport and at the time of slaughter (P < 0.01). Transporting pigs has been shown to cause stress in pigs (Pérez et al, 2002;Apple et al, 2005). Increases in plasma cortisol, glucose, lactate, and creatine phosphokinase are correlated with increased stress in pigs (Brown et al, 1998;Pérez et al, 2002;Apple et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Variations of cortisol, despite possible diurnal variations, and glucose (Table 3) suggest that short journeys did not permit a total recovery from the initial stress caused by loading, which is known to have a negative impact on the welfare of animals (Broom, 2000) independently from the loading method used (Brown et al, 2005). Furthermore, Bradshaw et al (1996) found a raise in cortisol levels 30 min after loading, and a gradual decrease after 4.5 h of transportation, and Apple et al (2005) found that cortisol levels matched up with an increase in plasmatic glucose. These assertions would justify our results, so that, in the case of short transportations, initial stress caused by sample size is provided between brackets *P < 0.05; **P < 0.01; ***P < 0.001; ns = non sgnificant Table 2).…”
Section: Discussionmentioning
confidence: 99%